Dysregulation and Therapeutic Targeting of RNA Splicing Variants in Cancer - Doaa Rabaya; Ghaleb Adwan (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
mRNA splicing constitutes a crucial biological phenomenon characterized by the excision of introns from pre-mRNA, followed by the synthesis of mature mRNA through the concatenation of the remaining exons. In eukaryotic cells, the process of alternative splicing introduces a diverse array of exon combinations, thereby exerting a significant influence on the generation of protein diversity. The occurrence of recurrent mutations during RNA splicing or within the core components of the spliceosome is implicated in the etiology and progression of diverse diseases, prominently including cancer. This review article scrutinizes the aberrations in RNA splicing linked to cancer and explores therapeutic endeavors directed at addressing mutations in RNA splicing.